Keterandalan Laporan Keuangan : Dampak dari Kualitas SDM dan Teknologi Informasi - Sri Dewi Anggadini; Vira Mutiara Subekti; Sari Damayanti; Egi Fahrana (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
This study aims to find out how much influence the quality of human resources and information technology on the reliability of financial statements. To produce reliable financial statements, a good quality of human resources and adequate information technology are required, to support the financial statements to be said to be reliable and valid. Lack of quality of human resources and information technology will affect reliability of its financial statements do not materialize. Method used in this study is descriptive and verificative method that is sourced in primary data with questionnaire collection techniques that are distributed to employees of the Financial and Asset Management Agency of West Bandung Regency. Due to small population, researchers determined sampling using Census Sampling, which is to make entire population into a sample with a total of 16 samples (respondents). Data processing conducted in form of statistical tests based on multiple regressions, as well as hypothesis tests using SPSS 23 application. Based on results of research conducted can be known quality of human resources is good but still have to be considered because there is still dishonesty in presentation of financial statements. Similarly, information technology applied is sufficient but still has to be considered about the software to always be updated and adapted to the needs. Conclusion of this study, Quality of Human Resources has a significant effect on Reliability of Financial Statements and Information Technology has a significant effect on Reliability of Financial Statements.